Environmental Factors at Mass-Gathering Events: Considerations for Health Research and Evaluation. Issue Volume 34:Issue s1(2019) (May 2019) - Hutton, Alison; Ranse, Jamie; Lund, Adam; Turris, Sheila; Munn, Brendan; Gray, Katy
Abstract : Introduction: This poster will document the environmental domain variables of a mass gathering. They include factors such as the nature of the event, availability of drugs or alcohol, venue characteristics and meteorological factors. Method: A systematic literature was used to develop a set of variables and evaluation regarding environmental factors that contribute to patient presentation rates. Results: Findings were grouped pragmatically into factors of crowd attendance, crowd density, venue, type of event, mobility, and meteorological factors. Discussion: This poster will outline a set of environmental variables for collecting data at mass gathering events. The authors have suggested that in addition to commonly used variables, air quality, wind speed, dew point, and precipitation could be considered as a data points to be added to the minimum standards for data collection.